Persepsi Masyarakat terhadap Penggunaan Transportasi Online Grab di Kota Jambi - Anisa Putri Risandra; Ade Nurdin; Yulia Morsa Said (Universitas Batanghari Jambi, 2023)
The more the population and development of technology that’s getting more advanced in Jambi City makes society about requires access to mobilization from somewhere else in a fast, and economic. With the advancement of technology and the need of transport, it is an online transport based transport that suits the needs of the people. The experience of driving using online transportation is very forming perception, especially the perception of user who is proven that it can affect the view of online transportation. This research aims to know the perception of society of online transport ini Jambi City. The data collection technique used is a survey method by using direct quisitioners and measured with Likert Scale with Microsoft Excel. TCR criteria or the community achievement level to the society’s perception for each inquiry is to the price of getting good result, security gets pretty good, time gets results well enough and accessibility get result well. With this to see the whole value or criteria of the community level of community or criteria to the extent of transport the online Grab ini Jambi City is by looking at the average of the five items that the perception of the TCR us quite well that the perception of the TCR is well enough that the perception of society is well enough that the perception of the online transport is well enough to be used by society as transportation that can be used in daily activities.